Research handbook on legal pluralism and EU law - Davies, Gareth, 1970-; Avbelj, Matej; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2018)
The Research Handbook on Legal Pluralism and EU Law explores the phenomenon of overlapping legal systems within the European Union, the nature of their interactions, and how they deal with the difficult question of the legal hierarchy between them. The contributors reflect on the history, sociology and legal scholarship on constitutional and legal pluralism, and develop this further in the light of the challenges currently facing the EU. Addressing pluralism within policy areas such as EMU, migration, and external relations, and applying different perspectives - from the constitutionalist to the Foucauldian - this diverse collection of thinkers about EU law ask whether a pluralist perspective is part of the problem or part of the solution. Contributors offer both critical and positive assessments of the value of pluralist thinking in the EU whilst addressing major issues facing the EU now - Brexit, populism, migration, the Euro-crisis - and asking what lessons can be learned from and for pluralism. This Research Handbook will be invaluable reading for legal academics specialising in EU law, EU constitutional Law, legal theory and political scientists focused on legal aspects of EU integration. Students on advanced courses in EU law and EU constitutional law, as well as judges at the Court of Justice and higher national courts, will also find this stimulating reading.
1. Introduction / Matej Avbelj, Gareth Davies -- Part I: The nature of european legal pluralism -- 2. Claim-making and parallel universes: legal pluralism from church and empire to statehood and the European Union / Poul Fritz Kjaer -- 3. Subverting sovereignty's voluntarism: pluralism and subsidiarity in cahoots / Maria Cahill -- 4. From pluralism to perspectivism / Kaarlo Tuori -- Part II: Theorizing EU constitutional pluralism -- 5. The anatomy of constitutional pluralism in the European Union / Cormac Mac Amhlaigh -- 6. Constitutional conflicts and agonistic pluralism: what can we learn from political theory? / Giuseppe Martinico -- 7. Human dignity and EU legal pluralism / Matej Avbelj -- 8. Constitutional pluralism beyond monism and dualism / François-Xavier Millet -- 9. Triangular constitutionalism: the consequences of constitutional pluralism for domestic constitutional thought / Tom Flynn ---10. The sociological concept of EU constitutional pluralism / Jíří Přibáň -- Part III: EU legal pluralism and democracy -- 11. Pluralism through its denial: the success of EU citizenship / Dimitry Kochenov and Justin Lindeboom -- 12. The false promise of constitutional pluralism / Nik de Boer -- 13. The metabolic constitution and the limits of EU legal pluralism / Peter Lindseth -- 14. Of politics and pluralism: governmentality and the EU legal order / Jessica Lawrence -- 15. The pluralist character of the European treaties / Clemens Kaupa -- Part IV: The practice of EU legal pluralism and its future -- 16. Is there room for legal pluralism in EU relations with third states?: a study of nordic approaches to European integration / Päivi Leino and Liisa Leppävirta -- 17. Constitutional pluralism and judicial adjudication: on legal reasoning, minimalism and silence by the court of justice / Suvi Sankari -- 18. Interpretative pluralism within EU law / Gareth Davies ---19. Discretion, not rules: post-unitary constitutional pluralism in the economic and monetary union / Matthias Goldmann -- 20. The EU's Relationship to international law: lessons from Brexit / Pavlos Eleftheriadis -- 21. Legal pluralism in the European regulation of border control: disassembling, diffusing, and legalising the power to exclude / Galina Cornelisse -- 22. The dangers of constitutional pluralism / R. Daniel Kelemen -- Afterword -- 23. Pluralism then and now / Neil Walker -- Index.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: pluralismus; evropské právo; pluralism; European law; země Evropské unie; European Union countries; e-knihy online; e-books online